Large Hemorrhagic Extrascleral Ciliary Body Melanoma Recurrence Treated With Transarterial Embolization and Coiling Followed by Exenteration. Issue 5 (September 2021) - Weber, Johannes; Flatz, Lukas; Sommacal, Andreas; Varde, Meghana Anika
Abstract : A 59-year-old male patient who suffered from a systemically metastasized, large extrascleral uveal melanoma recurrence of the left eye presented with active hemorrhage from the tumor. He had undergone proton beam irradiation for an epithelioid ciliary body melanoma 4 years before presentation and was lost to follow-up. Magnetic resonance angiography showed vascularization of the lesion via the ophthalmic and maxillary artery. Selective transarterial embolization of the tumor was conducted with polyvinyl alcohol microparticles followed by coiling of the supplying arteries. The bleeding stopped after 2 days and the tumor started to become necrotic. As tumor removal was the primary wish of the patient at this point in time, exenteration was carried out a week later without significant blood loss, intraoperative or postoperative complications. Socket healing was adequate, and the patient reported improved quality of life. He refused systemic palliative treatment and died 3 months after the intervention. Abstract : A 59-year-old man with metastasized, large extrascleral melanoma recurrence of the left eye presented with active hemorrhage from the tumor. Bleeding was managed with transarterial embolization and coiling before exenteration.